Serum Sickness-Like Reaction Associated with Epstein - Barr Virus: Clinical Case - Vladislav V. Ivanchikov; Nikolay N. Murashkin; Eduard T. Ambarchian; Anastasia D. Kuzminova ("Paediatrician" Publishers LLC, 2022)
Background. Annular dermatoses are a group of diseases with major clinical manifestation of rashes of relevant form. This manifestation pattern causes difficulties in diagnosis. The case of rarely diagnosed annular dermatosis is presented: serum siknesslike reaction (SSLR) triggered by the Epstein - Barr virus (EBV).Clinical case description. Patient D., 8 years old girl, noted abdominal pain 3 weeks before hospitalization, and later numerous polymorphic rashes (erythematous macules, urticarial elements), swelling and pain in joints. Self-treatment with non-steroidal anti-inflammatory and systemic antihistamines did not lead to any improvement. The patient was hospitalized in the pediatric department at the place of residence, where the diagnosis "Henoch-Schonlein purpura, mixed type" was established according to the results of physical, laboratory (double increase of ALT and AST, ESR up to 166 mm/h, IgM to EBV), and ultrasound (mesenteric lymph nodes hyperplasia) studies. Systemic glucocorticosteroids have led to improvement, however, few days after the end of the treatment there was relapse of rash and arthralgia. Thus, the girl was administrated to clinical diagnostic center. Patient's general condition was satisfactory at the time of examination. There were numerous erythematous annular urticarial and macular elements (3-12 cm) on the skin of face, body and limbs. Some foci, as well as some resolved rashes had blue spots with indistinct boundaries that disappeared after compression. Mucous membranes, nails and hair were intact. Subjective symptoms - slight burning around rashes, at palpation - low-intensity pain in the left radiocarpal joint. Blood tests: C-reactive protein concentration increased up to 12 mg/L, ESR up to 26 mm/h, IgG to EBV up to 47.7.Conclusion. During differential diagnosis we should consider the possibility of SSLR development in all pediatric patients with annular rashes associated with arthralgia and/or arthritis, fever, history of drug use (most often beta-lactam antibiotics), recent vaccination or manifestations of viral infection, especially in case of cyanotic spots after rashes resolution and non-specific laboratory parameters.